La perspectiva ecológica y el discurso teórico de la educación - García Carrasco, Joaquín (Teoría de la Educación. Revista Interuniversitaria, 2009)
The concept of the environment has been paid special attention by the field of ecology and its study has been approached using analytical and explanatory criteria, while at the same time maintaining a protectionist attitude that is also in favour of a sustainable development. In this study the environment is taken as a perspective from which to study the Total Agent of educational processes. Using this approach, reasons were found for reconstructing the function of space in educational strategies, the role of the «outside » in institutional processes and the function of the complementary in curricular plans and designs. Intervention with respect to the enviroment, to situations, is constituted as a mechanism for promoting educational effects in subjects and a new field of responsabilities to be responded to culturally.